Use of breathing exercises of E. Strelnikova in physical rehabilitation of patients with stenocardia pectoris - Волкова [Volkova S.] Світлана Степанівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!–[if gte mso 9]> 1024x768 <![endif]–> Shows the effects of breathing exercises conducted by the method E. Strelnikovoy on functional status of patients with stenocardia pectoris. It was assumed that systematic studies breathing exercises will help reduce angina attacks in patients. The study included 40 patients aged 52–56 years with a diagnosis of coronary heart disease. Found that the use of breathing exercises on E. Strelnikovoy positive impact on the health of patients. Proved that physical rehabilitation help normalize blood pressure and reduce stenocardia attacks during the day. <!–[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>